2020
DOI: 10.1101/2020.09.01.278747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating across neuroimaging modalities boosts prediction accuracy of cognitive ability

Abstract: Variation in cognitive ability arises from subtle differences in underlying neural architectural properties. Understanding and predicting individual variability in cognition from the differences in brain networks requires harnessing the unique variance captured by different neuroimaging modalities. Here we adopted a multi-level machine learning approach that combines diffusion, functional, and structural MRI data from the Human Connectome Project (N=1050) to provide unitary prediction models of various cogniti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 57 publications
7
28
5
Order By: Relevance
“…Accordingly, combining across modalities, as long as they are available, in one model seems to capture additional variance in the test data that cannot be achieved even by the best modality in the model. This is consistent with previous studies showing the enhanced predictive power of the stacked mode 12,21 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Accordingly, combining across modalities, as long as they are available, in one model seems to capture additional variance in the test data that cannot be achieved even by the best modality in the model. This is consistent with previous studies showing the enhanced predictive power of the stacked mode 12,21 .…”
Section: Discussionsupporting
confidence: 93%
“…It is possible, for instance, that the G-Factor depends not only on the activity of certain areas during certain cognitive tasks, such as working memory 11,12 , (task-based functional MRI; task-fMRI) but also on the intrinsic functional connectivity between different areas [13][14][15] (resting-state fMRI; rs-fMRI) as well as the anatomy of grey 16 (structural MRI; sMRI) and white 17,18 (Diffusion Tensor Imaging; DTI) matter. Recent studies in adults 19,20 have shown advantages of the multimodal approach in the prediction of the G-Factor that might outweigh the higher complexity of the models. Still, few, if any, multimodal studies have been done in children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial pattern of structure-function dependencies relating to cognition presented similarities both with the decoding network in lower-order somatomotor and association cortices, intrinsically characterized by strong structure-function coupling 25 , as well as with the fingerprinting network in fronto-parietal regions, characterized by weak structure-function interplay 25 . Recent work showed that structural and functional connectivities present distinct patterns of inter-individual variance as they relate to cognition 39,40 . Intriguingly, our results extend these findings identifying in the structure-function dependency a possible link between (divergent) structural and functional connectivity patterns in predicting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted a transmodal approach to stacking learning for prediction of CA-IMT 18,19 . In machine learning, stacking is classified as an ensemble learning method and involves combining predictions from a set of models into a new meta feature matrix for subsequent input into a new model for final prediction 20,26 .…”
Section: Multimodal Prediction Of Imtmentioning
confidence: 99%